EL PANEGÍRICO POÉTICO LATINO A PARTIR DE AUGUSTO: ALGUNAS CALAS - Estefanía Álvarez, Dulce (Myrtia, 1998)
The present work shows the particular significance that the panegiric had within the Latin literature as a literary genre. After reviewing its origins, the author particulary focuses her work on those testimonies provided by Claudianus.